The Free Zinc Concentration in the Synaptic Cleft of Artificial Glycinergic Synapses Rises to At least 1 μM - Zhang, Yan; Keramidas, Angelo; Lynch, Joseph W. (Frontiers in Molecular Neuroscience, 2016)
Zn2+ is concentrated into presynaptic vesicles at many central synapses and is released into the synaptic cleft by nerve terminal stimulation. There is strong evidence that synaptically released Zn2+ modulates glutamatergic neurotransmission, although there is debate concerning the peak concentration it reaches in the synaptic cleft. Glycine receptors (GlyRs), which mediate inhibitory neurotransmission in the spinal cord and brainstem, are potentiated by low nanomolar Zn2+ and inhibited by micromolar Zn2+. Mutations that selectively ablate Zn2+ potentiation result in hyperekplexia phenotypes suggesting that Zn2+ is a physiological regulator of glycinergic neurotransmission. There is, however, little evidence that Zn2+ is stored presynaptically at glycinergic terminals and an alternate possibility is that GlyRs are modulated by constitutively bound Zn2+. We sought to estimate the peak Zn2+ concentration in the glycinergic synaptic cleft as a means of evaluating whether it is likely to be synaptically released. We employed ‘artificial’ synapses because they permit the insertion of engineered  GlyRs with defined Zn2+ sensitivities into synapses. By comparing the effect of Zn2+ chelation on glycinergic IPSCs with the effects of defined Zn2+ and glycine concentrations applied rapidly to the same recombinant GlyRs in outside-out patches, we inferred that synaptic Zn2+ rises to at least 1 M following a single presynaptic stimulation. Moreover, using the fast, high-affinity chelator, ZX1, we found no evidence for tonic Zn2+ bound constitutively to high affinity GlyR binding sites. We conclude that diffusible Zn2+ reaches 1 M or higher and is therefore likely to be phasically released in artificial glycinergic synapses.